CHANGES IN THE ETHNO-CULTURAL IDENTITY OF DUNGANS OF UZBEKISTAN (IN THE EXAMPLE OF THE DUNGAN LANGUAGE) - Yosin , Abdulbokiyevich Ortikov (Educational Research in Universal Sciences, 2023)
This article analyzes the role of language as a fundamental issue in the understanding of ethno-cultural identity of the Dungans, one of the special diasporas in Uzbekistan. The national language has always been relevant, especially in a small number of nations. That is why national language is considered as the most important issue in a small number of nations compared to other nations. Among these few nationalities, the Dungans of Uzbekistan are also trying to preserve their national language. Today’s problems of the Dungans of Uzbekistan related to the national language and the scientific basis of their solution are also described in this article.